Pedestrian and Cyclists Impacts on vehicular Capacity and Emissions at different Turbo-roundabouts layouts - Coelho, Margarida C. (2018)
Presence of pedestrian crosswalks and cyclists at innovative configurations of roundabouts may result in an impedance effect on the available vehicular capacity of the intersection. The degree of this impedance is related to the likelihood of driver yielding at the crosswalk or bicycle dedicated lanes perpendicular to the movements of motor vehicles. However, little is known about the impedance effect and increase in emissions regarding the presence of pedestrians and cyclists at different turbo-roundabout layouts. The main objective of this paper is to quantify pedestrian and cyclist impacts on a turbo-roundabout corridor level. The study has two major purposes: 1) to evaluate the impact of several pedestrian and cyclists demands on corridor traffic performance and pollutant emissions; 2) to examine the effect of different driver yielding behaviour rates on both cyclist and pedestrian delay. Vehicle dynamics along with traffic, pedestrian and bicycle volumes data were collected from two turbo-roundabout corridors in the Netherlands. Microscopic modelling platforms of traffic (VISSIM) and emissions (Vehicle Specific Power and EMEP/EEA) were used to reproduce sites operations. Next, 72 combined pedestrian and cyclist demand scenarios according the corridor-specific characteristics were defined. Each volume scenario was then applied to scenarios with yielding rates of 100%, 80%, 60% and 40%.